The structure of the Orekhovo-Pavlograd suture zone by paleogeographic, geological and geophysical data - Yesypovych, Stanislav; Tovstyuk, Zinaida; Golovashchuk, Olena; Rybak, Olena; Skopenko, Olena; Romashko, Galina; Lazarenko, Iryna (Scientific Centre for Aerospace Research of the Earth Institute of Geological Science National Academy of Sciences of Ukraine, Kyiv, Ukraine, 2017)
The tectonic structure of the Orekhov-Pavlograd interblock zone of the Ukrainian shield is studied in this paper. This one has emerged since the 3600 million years ago, during the Katarchean/Archaean, ooidringed stage of the continental crust evolution. Its internal structure is described and anomalous features for future research are highlighted by comprehensive analysis of geological, geophysical, morphometric and remote sensed data.